Changes in salivary pH in patients with fixed orthodontics following the use of two types of mouthwashes - Andrea Monges-López; Claudia Núñez-Mongelós; Carlos Gabriel Adorno; Simón Cabañas-Pereira (Editorial Ciencias Médicas, 2022)
Introduction: Mouthwashes contribute to the inhibition of bacterial plaque formation and, therefore, may help to maintain salivary pH close to neutral. Objective: To identify changes in salivary pH in patients with fixed orthodontics after using a Stevia rebaudiana Bertoni solution and a commercial essential oil mouthwash. Methods: A clinical experiment with a mixed factorial design was carried out in patients with fixed orthodontic appliances. Once informed consent was signed, thirty-two patients were randomly assigned to one of 2 groups: 2 % S. rebaudiana B. solution or a commercial essential oil mouthwash. Fifteen ml of mouthwash was used for 60 s in all patients. Salivary pH was measured by two independent calibrated observers using pH-measuring paper before rinsing (basal measurement) and after rinsing, after 5 and 20 min. The data were analyzed by mixed ANOVA. Results: A statistically significant interaction was found between the type of treatment and the time of pH measurement. The medium pH of the S. rebaudiana and essential oil groups were respectively as per basal measurement: 6.61 and 6.52 (p = 0.72); after 5 min: 7.61 and 7.77 (p = 0.40); and after 20 min: 7.72 and 6.82 (p < 0.001). Conclusions: Both mouthwashes had the effect of increasing salivary pH to alkaline levels after 5 min, but only the 2 % S. rebaudiana B. mouthwash maintained the basic pH after 20 min.